Papa Roma - Lopes, Rodrigo Seco (Portugal, 2013)
The film focuses on Americans from Mississippi as they view the interactions of ordinary Romans. There are women disappointed with men and others who are in love. There is a Greek telling stories of popes and a Roman talking about his city.
Verzio Film Festival Submission
Verzio Film Festival Submission
Keywords: Documentary films